Electroacupuncture Prevent and Treat Perioperative Cognitive Impairment in Elderly Patients Undergoing Hip Surgery: A Protocol for a Randomized Controlled Trial - Fang Q; Xie J; Zheng S; Hou Y; Wu M; Chen Y; Yang Y; Wang G; Li J (Journal of Pain Research)
Qinqin Fang,1,* Jing Xie,1,* Shiyu Zheng,1,* Yuchao Hou,1 Mengdie Wu,1 Yijing Chen,2 Yuechang Yang,3 Gengqi Wang,4 Jing Li1 1Department of Acupuncture, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Anesthesiology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3Department of Preventive Medicine, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 4Department of Orthopedic Trauma, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gengqi Wang, Department of Orthopedic Trauma, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China, Email wanggengqi@126.com Jing Li, Department of Acupuncture, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China, Email LIJINGacu@126.comBackground: Electroacupuncture is effective in treating perioperative neurocognitive disorder (PND) and has good application prospects in the prevention and treatment of PND. However, the mechanism of electroacupuncture treatment for PND is comparatively unexplored.Methods/Design: This is a single-center clinical, prospective randomized controlled clinical trial protocol. 180 patients will be randomly divided into the treatment group and the control group in a ratio of 1:1. Both groups of subjects received routine care, while the treatment group will receive electroacupuncture treatment twice a day for 10 days. Acupoints will include Baihui (DU20), Shangxing (DU23), Yintang (EX-HN3), Meichong (BL3), Fengchi (GB20), Cuanzhu (BL2), Laogong (PC8), Hegu (LI4), and Zusanli (ST36). The primary outcome measure is the Mini-mental State Examination (MMSE). And the secondary outcome measures are the Confusion Assessment Method (CAM), Visual Analog Scale (VAS), Pittsburgh Sleep Quality Index (PSQI), Generalized Anxiety Disorder (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), neuron-specific enolase (NSE), superoxide dismutase (SOD), central nervous system-specific protein (s100-β) in serum. The outcome measures will be evaluated at baseline, during treatment and 1 week after treatment. What’s more, the incidence of non-delirium complications and mortality within 30 days will also be measured.Discussion: Results of this trial are expected to clarify the value of electroacupuncture performed on perioperative cognitive impairment in elderly patients undergoing hip surgery.Ethics: This trial has been approved by the Ethics Committee of Yueyang Hospital of Integrated Traditional Chinese and Western Medicine (No.2024– 037).Trial Registration: International Traditional Medicine Clinical Trial Registry, ITMCTR2024000298 (http://itmctr.ccebtcm.org.cn/), registered on 25 August, 2024. The trial will comply with the Declaration of Helsinki.Keywords: protocol, electroacupuncture, perioperative cognitive impairment, elderly patients